2012
DOI: 10.1021/ie301227t
|View full text |Cite
|
Sign up to set email alerts
|

Gas Holdup, Axial Dispersion, and Mass Transfer Studies in Bubble Columns

Abstract: This article presents an extensive study on the gas holdup, axial liquid dispersion, and mass transfer for packed, trayed, and empty bubble columns. Four types of structured packings (Super-Pak, Flexipac, Mellapak, and Gauze) and two types of perforated partition trays (with 25% and 40% tray open area) were used to characterize the packed and trayed bubble columns, respectively. It was observed that the gas holdup and mass transfer characteristics of the packed and trayed bubble columns are superior to those o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 39 publications
2
39
1
2
Order By: Relevance
“…Baawain et al [121], showed that the counter-current or co-current operating mode influenced ε G for about 5% of its weight, and less than 1% of its bubble size, showing that the effect observed is mainly caused by the bubble rise velocity and not only caused by the bubble size. In agreement with this explanation concerning the influence of U L on bubble motion, different studies have reported ε G decreasing in co-current operations [49,90,[122][123][124][125][126][127][128] and increasing in counter-current operations [48,49,128]. Biń et al [128] compared the three-operation mode showing that ε G increases with U L in counter-current mode and decreases or remains constant in co-current mode.…”
Section: Influence Of the Bubble Column Operationmentioning
confidence: 59%
See 1 more Smart Citation
“…Baawain et al [121], showed that the counter-current or co-current operating mode influenced ε G for about 5% of its weight, and less than 1% of its bubble size, showing that the effect observed is mainly caused by the bubble rise velocity and not only caused by the bubble size. In agreement with this explanation concerning the influence of U L on bubble motion, different studies have reported ε G decreasing in co-current operations [49,90,[122][123][124][125][126][127][128] and increasing in counter-current operations [48,49,128]. Biń et al [128] compared the three-operation mode showing that ε G increases with U L in counter-current mode and decreases or remains constant in co-current mode.…”
Section: Influence Of the Bubble Column Operationmentioning
confidence: 59%
“…This method is based on the measurement of the liquid free surface before and after aeration. Another well-known method is based on the measurement of the differential pressure between two or more points in the column [80,86,114,116,122,123,125,126,135,141,170,179,194,198,209], under the hypothesis of negligible acceleration and friction pressure losses, as discussed by Leonard et al [1]. This method has been applied by a large number of authors.…”
Section: The Gas Hold-upmentioning
confidence: 99%
“…For example, Akita and Yoshida (1973) (d c ¼0.152 m, H c ¼2.5 m) observed a negligible effect of U L (up to 0.04 m/s) in both co-current and countercurrent operations. At higher liquid velocities, the column operation influences the holdup: the co-current mode reduces the holdup (Biń et al, 2001;Chaumat et al, 2005b;Jin et al, 2007;Kumar et al, 2012;Otake et al, 1981;Pjontek et al, 2014;Shah et al, 2012;Simonnet et al, 2007), and the counter-current mode increases the holdup (Besagni and Inzoli, 2016a;Besagni et al, 2014Biń et al, 2001;Jin et al, 2010;Otake et al, 1981) as bubbles are either accelerated or decelerated by liquid motion (Leonard et al, 2015;Rollbusch et al, 2015a). Baawain et al (2007) showed that the counter-current or cocurrent operation modes influenced the holdup by approximately 5% in weight, and less than 1% in bubble size, showing that the effect observed is mainly caused by the bubble rise velocity and not only the bubble size.…”
Section: Introductionmentioning
confidence: 99%
“…In a series of recently published papers, the researchers describe a novel process for the synthesis of unsaturated polyester based on reactive distillation ( Figure 6.6 a, b, c) [17À21]. Reactive distillation combines the preparative step (synthesis) and the down-streaming step (separation) into one single operating unit and represents one of the most important applications of the multifactorial reactor concept [22].…”
Section: Process Intensification By Reactive Distillationmentioning
confidence: 99%
“…The glycolyzated PET fragments can be then co-reacted with fresh unsaturated diacids (or anhydrides) and blended with styrene to produce superficial reinforcing of plastics, varnishes, binder for glass fiber mats and other applications [7]. Figure 6.6 (a) Process intensification: transferring the synthesis of unsaturated polyesters from tach processes to a reactive distillation process [17]; (b) Process intensification: Principal setup of reactive distillation process for the production of unsaturated polyesters [18]; and (c) Process intensification: Photograph of pilot plant scale reactive distillation equipment for unsaturated polyester production [18].…”
Section: Introduction Of Bio-based and Recycled Raw Materialsmentioning
confidence: 99%